Maternal nutrition alters mRNA isoform expression, usage, and splicing dynamics in skeletal muscle of beef cattle offspring - Polizel, Guilherme Henrique Gebim; Cánovas, Ángela; Ramírez-Zamudio, Germán D.; Cesar, Aline Silva Mello; Diniz, Wellison J. S.; Ferraz, José Bento Sterman; Fukumasu, Heidge; Brito, Luiz F.; Carvalho, Felipe Eguti de; Santana, Miguel (Frontiers in Genetics, 2026)
BackgroundMaternal nutrition during gestation plays a critical role in fetal muscle development and long-term metabolic programming; however, its persistent molecular effects on offspring skeletal muscle remain unclear. Therefore, the main objective of this study was to investigate the influence of prenatal nutrition on long-term differential gene expression (DGE), differential mRNA transcript expression (DTE), and differential transcript usage (DTU) in skeletal muscle of beef cattle.MethodsA total of 126 pregnant Nellore cows were assigned to three dietary treatments: mineral supplementation only (NP), protein-energy supplementation during late gestation (PP), and protein-energy supplementation throughout gestation (FP). At 676 ± 28 days of age, muscle samples were collected from offspring for RNA sequencing. The DGE and DTE analyses were performed using the edgeR package, while DTU was evaluated with the IsoformSwitchAnalyzeR package. Over-representation analysis was conducted using g:Profiler.ResultsA total of 27,412 genes and 111,185 transcripts, including novel loci and isoforms were identified. Gene-level differences were modest (16 genes), whereas transcript-level analyses revealed stronger effects, with a higher number of significant expression and usage changes across conditions. The FP × NP comparison exhibited the greatest impact on gene expression, with 14 DTEs and 87 DTUs, compared with 12 and 30 in PP × NP, and 10 and three in FP × PP, respectively. Isoform switching was observed in key genes including SLC7A8, SLC25A30, SORBS3, and CDH13 genes, influencing coding potential, functional domains, and mRNA stability, with potential consequences for amino acid transport, cytoskeletal organization, and muscle regeneration. Functional enrichment analyses highlighted significant metabolic pathways related to amino acid and biotin metabolism, intracellular trafficking, and immune regulation.ConclusionOverall, prenatal nutrition, particularly protein-energy supplementation throughout gestation in comparison to mineral supplementation, modulates offspring muscle mainly through transcript usage and splicing, suggesting long-term adaptive mechanisms beyond gene-level regulation.